2022
DOI: 10.1101/2022.07.21.501021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IMC-Denoise: a content aware denoising pipeline to enhance Imaging Mass Cytometry

Abstract: Imaging Mass Cytometry (IMC) is an emerging multiplexed imaging technology for analyzing complex microenvironments that has the ability to detect the spatial distribution of at least 40 cell markers. However, this new modality has unique image data processing requirements, particularly when applying this technology to patient tissue specimens. In these cases, signal-to-noise ratio for particular markers can be low despite optimization of staining conditions, and the presence of pixel intensity artifacts can de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…MD reflects the overall diffusion of water molecules in the tissues, the bigger MD indicates the less restriction for diffusion in tissues. FA and MD are defined as follows FAbadbreak=12(λ1λ2)2+(λ1λ3)2+(λ2λ3)2λ12+λ22+λ32$$\begin{equation}FA = \sqrt {\frac{1}{2}} \frac{{\sqrt {{{({\lambda _1} - {\lambda _2})}^2} + {{({\lambda _1} - {\lambda _3})}^2} + {{({\lambda _2} - {\lambda _3})}^2}} }}{{\sqrt {\lambda _1^2 + \lambda _2^2 + \lambda _3^2} }}\end{equation}$$ MDbadbreak=false(λ1+λ2+λ3false)3$$\begin{equation}MD = \frac{{({\lambda _1} + {\lambda _2} + {\lambda _3})}}{3}\end{equation}$$where λ 1 , λ 2 , and λ 3 indicate three eigenvalues of the DT, respectively 29,30 . FO reflects the arrangement pattern of cardiac myocytes, which is determined by the direction of the eigenvector associated with the largest eigenvalue of the DT.…”
Section: Denoising Principle Of Ssecnn Methodsmentioning
confidence: 99%
“…MD reflects the overall diffusion of water molecules in the tissues, the bigger MD indicates the less restriction for diffusion in tissues. FA and MD are defined as follows FAbadbreak=12(λ1λ2)2+(λ1λ3)2+(λ2λ3)2λ12+λ22+λ32$$\begin{equation}FA = \sqrt {\frac{1}{2}} \frac{{\sqrt {{{({\lambda _1} - {\lambda _2})}^2} + {{({\lambda _1} - {\lambda _3})}^2} + {{({\lambda _2} - {\lambda _3})}^2}} }}{{\sqrt {\lambda _1^2 + \lambda _2^2 + \lambda _3^2} }}\end{equation}$$ MDbadbreak=false(λ1+λ2+λ3false)3$$\begin{equation}MD = \frac{{({\lambda _1} + {\lambda _2} + {\lambda _3})}}{3}\end{equation}$$where λ 1 , λ 2 , and λ 3 indicate three eigenvalues of the DT, respectively 29,30 . FO reflects the arrangement pattern of cardiac myocytes, which is determined by the direction of the eigenvector associated with the largest eigenvalue of the DT.…”
Section: Denoising Principle Of Ssecnn Methodsmentioning
confidence: 99%
“…These thresholds were then used in R script to binarize the KI67 and ZEB1 intensities into ZEB1 and KI67 positive and negative cell populations that were then used in further analysis. The images were prepared for visualization by using IMC denoise pipeline as described in work by Lu et al( 5 ).…”
Section: Supplementary Methods and Materialsmentioning
confidence: 99%
“…There are a number of published "end to end" pipelines for IMC data analysis (8)(9)(10)(11)(12) that utilise open source software for segmentation such as Ilastik (13) and CellProfiler (14,15), as well as StarDist (16) and IMC-specific approaches that utilise deep learning (17). There have also been attempts to use matched fluorescent images of the nuclei using DAPI co-staining to improve segmentation accuracy (18) as well as removing image noise (19,20). Nonetheless, it has been shown that, due to the nature of tissue imaging, simple approaches to single cell segmentation are often highly effective (21).…”
Section: Introductionmentioning
confidence: 99%